Thrombosis and hemorrhage in diabetic retinopathy: a perspective from an inflammatory standpoint - Murugesan, Nivetha (Semin Thromb Hemost, 2015)
Retinal ischemia and hemorrhage are hallmarks of worsening diabetic retinopathy, which can lead to neovascularization, macular edema, and severe vision loss. Although diabetes alters expression of clotting factors and their activities, and increases retinal microthromboses, the effects of thrombotic processes on the pathogenesis of diabetic retinopathy are not fully understood. In addition to the roles of coagulation and fibrinolytic cascades in thrombosis and hemostasis, components in these systems also mediate multiple effects on the vasculature that promote inflammation. Plasma kallikrein, thrombin, and urokinase are increased in diabetic retinopathy and exert proinflammatory effects that contribute to retinal vascular dysfunction. The accumulation and activation of these and additional coagulation factors in the vitreous due to hemorrhage and chronic retinal injury in the diabetic retina may contribute to worsening of retinal inflammation and capillary dysfunction, which lead to retinal ischemia and edema. Further understanding of the role for specific coagulation factors in diabetic retinopathy may suggest new therapeutic opportunities for this vision-threatening disease.